Carbon-modified alumina carrier, catalyst, preparation method of carbon-modified alumina carrier and catalyst, and method for deeply removing trace CO

By preparing a carbon-modified large specific surface area alumina support and supporting active components, the problems of low loading of alumina support and low dispersion of active metals in the prior art are solved, and efficient catalyst preparation and trace CO removal effects are achieved.

CN119524845AActive Publication Date: 2025-02-28CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202311079130.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-25
Publication Date
2025-02-28
Estimated Expiration
2043-08-25

AI Technical Summary

Technical Problem

In the prior art, there are fewer aluminum oxide carriers on the larger surface and are difficult to prepare, resulting in low catalyst loading and low dispersion of active metals.

Method used

By preparing a carbon-modified large specific surface area alumina support, impregnation and calcination are performed using a nitrogen-containing polymer solution to improve the specific surface area and pore volume of the support, and the active components are supported on the support to form an efficient catalyst.

Benefits of technology

While the catalyst load is large, the active metal has high dispersion, high reaction activity and good stability, and can effectively remove trace CO at a lower reaction temperature.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004413690180000101
    Figure BDA0004413690180000101
  • Figure BDA0004413690180000111
    Figure BDA0004413690180000111
  • Figure BDA0004413690180000121
    Figure BDA0004413690180000121
Patent Text Reader

Abstract

The invention provides a carbon-modified alumina carrier, a catalyst, a preparation method of the carbon-modified alumina carrier, a preparation method of the catalyst and a method for deeply removing trace CO. The specific surface area of the alumina carrier is greater than or equal to 300m < 2 > / g, and the pore volume is 1.0-3.5 m < 3 > / The preparation method comprises the following steps: preparing sodium hydroxide and sodium metaaluminate into a sodium metaaluminate solution, adding the sodium metaaluminate solution into an aluminum sulfate solution to obtain a boehmite precursor, crystallizing to obtain boehmite, adding the boehmite into a nitrogen-containing polymer solution, dipping, reacting, and roasting the obtained reaction product in a protective gas atmosphere to obtain the nitrogen-containing polymer. The carbon modified alumina carrier is obtained; and contacting the carbon-modified alumina carrier with an impregnation liquid containing an active component, taking out the impregnated carbon-modified alumina carrier, and carrying out second roasting in a protective gas atmosphere to obtain the catalyst, and carrying out contact reaction on a material containing CO and the obtained catalyst to remove CO. According to the prepared catalyst, the large specific surface of the carrier enables the loading capacity of the catalyst to be large, and the dispersity of active metal is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalysts, and more particularly to a carbon-modified alumina carrier, a catalyst, a preparation method thereof, and a method for deeply removing trace amounts of CO. Background Art

[0002] Alumina-supported catalysts have been widely used in petrochemical plants. The carrier in the catalyst can increase the mechanical strength of the catalyst, reduce the wear of the catalyst, increase the specific surface area of ​​the catalyst, help the good dispersion of the active components, and can also play the role of a co-catalyst. Activated alumina is a porous, highly dispersed solid material with high crushing strength, moderate specific surface area, adjustable pore size and pores, good adsorption performance, wide crystal phase temperature range, and acidic surface. It has become one of the most widely used catalysts or catalyst carriers in the chemical and petroleum industries, and plays an important role in the cracking, hydrorefining, hydrodesulfurization, reforming of hydrocarbons to produce hydrogen, and purification of automobile exhaust. Structure is one of the important properties of catalyst carriers. The important metrics for describing the pore structure of a substance include specific surface area, pore volume, average pore size, and pore distribution. The catalytic reaction takes place on the surface of the catalyst. The specific surface area plays an important role in the dispersion of the active components of the catalyst, and the dispersion of the active components is closely related to the catalytic activity. The pore volume is the sum of the volume of all pores per unit mass of the catalyst, which is closely related to the stability and life of the catalyst. The pore size and pore type will affect the internal diffusion rate of reactants and products, thereby affecting the activity and selectivity of the catalyst. As a catalyst carrier, a high specific surface area and rich pore structure provide active sites and access channels for the reaction, which is a necessary requirement for improving reaction efficiency. The catalyst performance is not only affected by the specific surface area and total pore volume of the catalyst, but also by the pore size and its distribution. Large pore volume is conducive to the diffusion of macromolecular compounds into the interior of the catalyst particles, realizing the hydrogenation conversion process of macromolecules, and high specific surface area is conducive to the diffusion of active metals, thereby increasing the performance of the catalytic catalyst. The large pore structure can improve the selectivity of the reaction, make the most effective use of the active sites in the pores, and improve the activity of the catalyst. At the same time, the large pore structure has a certain inhibitory effect on the coking that may appear on the catalyst surface, thereby extending the life of the catalyst.

[0003] In the prior art, alumina carriers with large specific surface areas are rare and difficult to prepare. It is necessary to develop an alumina carrier with a large specific surface area so that the catalyst loading capacity is large and the metal dispersion is high. Summary of the invention

[0004] In order to solve the technical problems existing in the prior art, the present invention provides a carbon-modified alumina carrier, a catalyst and a preparation method thereof, and a method for deep removal of trace CO.

[0005] Compared with the impregnation method, the active metal particles obtained by the traditional preparation method are larger; however, the carrier loading capacity prepared by the impregnation method is low. The present invention solves the problem of low loading capacity of the traditional alumina carrier.

[0006] The present invention first prepares a large specific surface area alumina carrier, then contacts the large specific surface area alumina carrier with a nitrogen-containing polymer solution, then performs a first roasting on the contact product under an inert atmosphere to obtain a carrier, and finally loads the active component on the carrier to obtain a catalyst. The carbon-modified large specific surface area alumina-loaded catalyst prepared by the present invention has a large specific surface area of ​​the carrier so that the catalyst loading amount is large and the active metal dispersion is high.

[0007] One of the objects of the present invention is to provide a carbon-modified alumina carrier.

[0008] The specific surface area of ​​the alumina carrier is ≥300m 2 / g, preferably 320 to 550 m 2 / g, more preferably 400 to 480 m 2 / g; pore volume is 1.0~3.5cm 3 / g, preferably 1.5 to 3.0 cm 3 / g.

[0009] The water absorption rate of the alumina carrier of the present invention is 110-160%, wherein the water absorption rate is tested as follows:

[0010] Weigh a fixed mass of alumina carrier m1 and place it in deionized water. After 10 minutes, absorb the water stains on the surface with absorbent paper and weigh the mass as m2. The water absorption rate is equal to (m2-m1) / m1.

[0011] The second object of the present invention is to provide a method for preparing a carbon-modified alumina carrier, comprising the following steps:

[0012] (1) preparing sodium aluminate solution by sodium hydroxide and sodium aluminate, adding the solution to an aluminum sulfate solution, and mixing the mixture to obtain a boehmite precursor;

[0013] (2) crystallizing the boehmite precursor obtained in step (1) to obtain boehmite;

[0014] (3) The boehmite obtained in step (2) is post-treated and added to a nitrogen-containing polymer solution, and reacted after impregnation. The obtained reaction product is calcined in a protective gas atmosphere to obtain the carbon-modified alumina carrier.

[0015] In a preferred embodiment of the present invention,

[0016] Step (1),

[0017] The concentration of aluminum ions in the sodium aluminate solution is 0.1 to 0.9 mol / L, preferably 0.3 to 0.9 mol / L; the molar ratio of sodium to aluminum in the sodium aluminate solution is (2 to 6):1, preferably (2 to 5):1;

[0018] The method of adding is dropwise addition;

[0019] The concentration of the aluminum sulfate solution is 0.1 to 0.9 mol / L, preferably 0.3 to 0.6 mol / L;

[0020] The amount of sodium aluminate solution added is until the pH value reaches 8 to 11;

[0021] The mixing temperature is 10-35° C., the mixing time is 10-60 min, and the mixing method is stirring. Preferably, the stirring speed is 200-800 rpm.

[0022] In a preferred embodiment of the present invention,

[0023] Step (2),

[0024] The crystallization temperature is 50 to 120°C, preferably 70 to 120°C;

[0025] The crystallization time is 2 to 24 hours; preferably 5 to 20 hours;

[0026] The crystallization is preferably carried out by hydrothermal crystallization.

[0027] In a preferred embodiment of the present invention,

[0028] Step (3),

[0029] The post-treatment methods include filtering, washing, and drying; filtering can be performed by general methods of the prior art, such as suction filtration, etc.; washing can be performed by general methods of the prior art, such as washing with deionized water for 3 to 5 times; drying can be performed by general methods of the prior art, such as drying in an oven, preferably, the drying temperature is 100 to 140° C., and the drying time is 2 to 8 hours;

[0030] The nitrogen-containing polymer is at least one of polyvinyl imidazole, polyvinyl pyrrolidone and polyvinyl pyridine;

[0031] The solvent in the nitrogen-containing polymer solution is at least one of methanol and ethanol;

[0032] The mass ratio of the boehmite to the nitrogen-containing polymer is (1-100):1, preferably (5-100):1, and more preferably (10-100):1;

[0033] The reaction temperature is 80-150°C, preferably 100-120°C;

[0034] The reaction time is 4 to 10 hours, preferably 5 to 10 hours;

[0035] The concentration of the nitrogen-containing polymer solution is 0.1 to 2 wt%, preferably 0.6 to 1.8 wt%;

[0036] The protective gas is nitrogen or an inert gas;

[0037] The immersion temperature is 10-35°C and the immersion time is 0.5-2h;

[0038] The calcination temperature is 400-600°C, and the calcination time is 3-10h.

[0039] The third object of the present invention is to provide a carbon-modified alumina carrier obtained by the above preparation method.

[0040] The fourth object of the present invention is to provide a catalyst, comprising a carbon-modified alumina carrier, the catalyst further comprising an active component, preferably further comprising an auxiliary component; further preferably,

[0041] The active component includes Cu;

[0042] The auxiliary agent component is at least one of Zn, Mg, Ni, Co, Mn, and Co;

[0043] More preferably,

[0044] Taking the total mass of the catalyst as 100%, the catalyst comprises:

[0045] Carbon-modified alumina support 30-90%; preferably 55-70%;

[0046] Active ingredient 10-60%; preferably 25-40%;

[0047] The auxiliary component is 0-10%, preferably 0-6%.

[0048] A fifth object of the present invention is to provide a method for preparing a carbon-modified alumina-supported catalyst, comprising:

[0049] The carbon-modified alumina carrier is contacted with a solution or a mixed solution containing an active component, preferably the solution or the mixed solution also includes an auxiliary component, and the carbon-modified alumina carrier after contact is taken out and then subjected to a second calcination under a protective gas atmosphere to obtain the carbon-modified alumina carrier catalyst.

[0050] In a preferred embodiment of the present invention,

[0051] The mixed solution containing the active component is a mixed solution composed of a solution containing the active component and a solution containing the auxiliary component; further preferably, the mass percentage of the water-soluble salt of the active component in the solution containing the active component is 30-60wt%; the mass percentage of the water-soluble salt of the auxiliary component in the solution containing the auxiliary component is 1-8wt%, preferably 4-6wt%;

[0052] The temperature of the solution or mixed solution containing the active component in contact with the carbon-modified alumina support is 15 to 40° C. and the time is 10 to 60 minutes;

[0053] The solution or mixed solution containing the active component is contacted with the carbon-modified alumina support by at least one of immersion and spraying;

[0054] The carbon-modified alumina support is contacted with a solution or a mixed solution containing active components, and the product is subjected to a second drying and then a second calcination; preferably, the temperature of the second drying is 100 to 130° C., and the time is 8 to 15 hours;

[0055] The protective gas is at least one of nitrogen and an inert gas; the inert gas is preferably at least one of argon and helium;

[0056] The second calcination is carried out at a temperature of 400 to 800° C. and for a time of 2 to 10 hours.

[0057] The sixth object of the present invention is to provide a catalyst obtained by the above preparation method.

[0058] The seventh object of the present invention is to provide a method for deep removal of trace CO, comprising:

[0059] The material containing CO is contacted with the catalyst to react and remove CO.

[0060] In a preferred embodiment of the present invention,

[0061] The CO content of the CO-containing material is 0.01 ppm to 200 ppm, preferably 0.01 to 100 ppm, more preferably 0.01 to 10 ppm, and most preferably 0.1 to 5 ppm;

[0062] The reaction temperature is 0 to 150°C, preferably 20 to 120°C;

[0063] The reaction pressure is 0.1 to 5 MPa, preferably 0.1 to 3 MPa;

[0064] The volume space velocity during gas phase reaction is 1000~10000h -1 ;

[0065] The volume space velocity during liquid phase reaction is 1 to 150 h-1 .

[0066] Compared with the prior art, the present invention has the following beneficial effects:

[0067] (1) The carbon-modified large-surface-area alumina-loaded catalyst has a higher surface area, high water absorption rate, large amount of adsorbed metal, and high loading capacity.

[0068] (2) The catalyst prepared by the impregnation method has higher metal dispersion and higher reaction activity, and can remove CO at a lower reaction temperature.

[0069] (3) The carbon-modified carrier will change the acidity and alkalinity of the catalyst surface, and the catalyst will have high stability. DETAILED DESCRIPTION

[0070] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the contents of the present invention still fall within the scope of protection of the present invention.

[0071] The raw materials used in the examples are all conventional commercially available raw materials.

[0072] Test method:

[0073] Measurement of water absorption rate: Weigh a fixed mass of alumina carrier m1 and place it in deionized water. After 10 minutes, absorb the water stains on the surface with absorbent paper and weigh the mass as m2. The water absorption rate is equal to (m2-m1) / m1.

[0074] Testing method for metal content: X-ray fluorescence spectroscopy (XRF) uses an X-ray photoelectron spectrometer from PA Nalytical BV of the Netherlands. The element composition and relative content of the sample surface are analyzed after vacuuming.

[0075] Example 1

[0076] (1) 22.56 g of NaOH and 17.5 g of sodium aluminate were dissolved in 250 ml of deionized water to prepare a sodium aluminate solution. 88.4 g of aluminum sulfate was dissolved in 500 ml of deionized water to prepare an aluminum sulfate solution. The prepared sodium aluminate solution was added dropwise to the prepared aluminum sulfate solution until the pH value was 9.0. The mixture was stirred at room temperature for 30 min at a stirring speed of 600 rpm to obtain a boehmite precursor.

[0077] (2) The obtained boehmite precursor is crystallized at 120° C. for 20 h to obtain boehmite with a large specific surface area.

[0078] (3) The obtained large specific surface area boehmite was filtered with deionized water at room temperature, washed with deionized water for 5 times, and dried in an oven at 120 degrees for 6 hours to obtain dry large specific surface area boehmite. 100g of the obtained large specific surface area boehmite was immersed in 100g of 1wt% ethanol solution of polyvinyl imidazole (containing 1g of polyvinyl imidazole) at room temperature for 0.5h, then transferred to a hydrothermal autoclave to react at 100°C for 10h, cooled and filtered, dried at 80°C for 4h, then placed in a nitrogen atmosphere, and calcined at 400°C for 10h to obtain a carbon-modified alumina carrier. The specific surface area of ​​the alumina carrier is 448m 2 / g, pore volume is 2.45cm 3 / g, and its water absorption was tested to be 150%.

[0079] (4) 20 g of the carrier was placed in a 43 wt % copper nitrate aqueous solution (wherein the amount of copper nitrate calculated as metallic element copper was 9.9 g) and immersed in equal volumes. After immersion at room temperature for 20 min, the carrier was taken out, drained, dried at 120° C. for 12 h, and calcined at 400° C. in a nitrogen atmosphere for 3 h to obtain a catalyst, wherein XRF characterization showed that the copper loading in the catalyst was 33 wt %.

[0080] Example 2

[0081] (1) NaOH and sodium aluminate are dissolved in deionized water to prepare a 0.4 mol / L sodium aluminate solution, wherein the molar ratio of sodium to aluminum is 5:1; aluminum sulfate is dissolved in deionized water to prepare a 0.4 mol / L aluminum sulfate solution; the prepared 0.4 mol / L sodium aluminate solution is added dropwise to the prepared 0.4 mol / L aluminum sulfate solution until the pH value is 10; the solution is stirred at room temperature for 50 min at a stirring speed of 400 rpm to obtain a boehmite precursor.

[0082] (2) The obtained boehmite precursor is crystallized at 80°C for 8 hours to obtain boehmite with a large specific surface area.

[0083] (3) The obtained large specific surface area boehmite was filtered with deionized water at room temperature, washed with deionized water for 5 times, and dried in an oven at 120 degrees for 6 hours to obtain dry large specific surface area boehmite. 100g of the obtained large specific surface area boehmite was immersed in 625g of 1.6wt% polyvinyl imidazole ethanol solution (containing 10g of polyvinyl imidazole) at room temperature for 1 hour, and then transferred to a hydrothermal autoclave to react at 120°C for 6 hours, cooled and filtered, dried at 80°C for 4 hours, and then placed in a nitrogen atmosphere and calcined at 600°C for 4 hours to obtain a carbon-modified alumina carrier. The specific surface area of ​​the alumina carrier is 469m 2 / g, pore volume is 2.51cm 3 / g, and its water absorption was tested to be 152%.

[0084] (4) 20 g of the carrier was placed in a 56 wt % copper nitrate aqueous solution (wherein the amount of copper nitrate calculated as metallic element copper was 12.8 g) and immersed in equal volumes. After immersion at room temperature for 40 min, the carrier was taken out, drained, dried at 120° C. for 12 h, and calcined at 700° C. for 8 h in a nitrogen atmosphere to obtain a catalyst.

[0085] XRF characterization showed that the copper loading in the catalyst was 39wt%.

[0086] Example 3

[0087] Steps (1) to (3) are the same as those in Example 1.

[0088] (4) 20 g of the carrier was placed in a mixed solution consisting of a 51 wt% copper nitrate aqueous solution and a 5 wt% magnesium nitrate solution (wherein the amount of copper nitrate calculated as metal element copper was 10.7 g, and the amount of magnesium nitrate calculated as metal element magnesium was 1.8 g), and after immersion at room temperature for 20 min, the carrier was taken out, drained, dried at 120° C. for 12 h, and calcined at 400° C. in a nitrogen atmosphere for 3 h to obtain a catalyst. XRF characterization showed that the copper loading in the catalyst was 33 wt% and the magnesium loading was 5.5 wt%.

[0089] Example 4

[0090] The difference from Example 3 is that the mixed solution is a 54wt% copper nitrate aqueous solution (wherein the amount of copper nitrate calculated as metal element copper is 11.0g) and a 5wt% zinc nitrate aqueous solution (wherein the amount of zinc nitrate calculated as metal element zinc is 1.3g);

[0091] Except for the above differences, other conditions in Example 4 are the same as those in Example 3 to obtain a catalyst.

[0092] XRF characterization showed that the copper loading in the catalyst was 34 wt % and the zinc loading was 4.0 wt %.

[0093] Comparative Example 1

[0094] The difference from Example 1 is that commercially available alumina is used as a carrier instead of the modified alumina carrier;

[0095] The specific surface area of ​​commercially available alumina carrier is 236m 2 / g, pore volume is 1.0cm 3 / g;

[0096] Except for the above differences, other conditions of Comparative Example 1 are the same as those of Example 1 to obtain a catalyst.

[0097] XRF characterization showed that the copper loading in the catalyst was 33 wt%.

[0098] Comparative Example 2

[0099] The difference from Example 3 is that commercially available alumina is used as a carrier instead of the modified alumina carrier;

[0100] The specific surface area of ​​commercially available alumina carrier is 236m 2 / g, pore volume is 1.0cm 3 / g;

[0101] Except for the above differences, other conditions of Comparative Example 2 are the same as those of Example 3 to obtain a catalyst.

[0102] XRF characterization showed that the copper loading in the catalyst was 25wt%, and the magnesium loading was 5.5wt%.

[0103] Comparative Example 3

[0104] The difference from Example 4 is that commercially available alumina is used as a carrier instead of the modified alumina carrier;

[0105] The specific surface area of ​​commercially available alumina carrier is 236m 2 / g, pore volume is 1.0cm 3 / g;

[0106] Except for the above differences, other conditions of Comparative Example 3 are the same as those of Example 4 to obtain a catalyst.

[0107] XRF characterization showed that the copper loading in the catalyst was 25wt%, and the zinc loading was 4wt%.

[0108] The catalysts prepared in Examples 1 to 4 and Comparative Examples 1 to 3 were used to carry out a carbon monoxide removal test and a continuous reaction test, as follows:

[0109] Carbon monoxide removal test:

[0110] Catalyst evaluation was carried out in a fixed bed continuous flow tubular reactor. The catalyst loading amount was 20 mL. After the catalyst was loaded, it was purged with air at 120°C for 12 h.

[0111] The material is a mixed gas containing 2.2ppmCO, the reaction pressure is 3.5MPa, the reaction temperature is 50℃, 90℃, and the space velocity is 3000hr -1 、4500hr -1 、10000hr -1 .

[0112] The raw materials and products were detected by gas chromatography Agilent 7890 with a nickel methanogen converter, a thermal conductivity detector and a hydrogen flame detector, with the minimum detection limit of carbon monoxide being 0.1 ppm, and by a trace carbon monoxide analyzer from AMETEK, with the minimum detection limit of carbon monoxide being 1 ppb.

[0113] The test data were collected after the reaction was stabilized for about 10 to 20 hours and are listed in Tables 1 to 2.

[0114] Continuous reaction test:

[0115] The large specific surface area alumina supported catalyst in Example 1 was used at a reaction pressure of 3.5 MPa, a reaction temperature of 90°C, and a space velocity of 3000 hr -1 , continuous reaction for 200h.

[0116] The raw materials and products were detected by gas chromatography Agilent 7890 with a nickel methanogen converter, a thermal conductivity detector and a hydrogen flame detector, with the minimum detection limit of carbon monoxide being 0.1 ppm, and by a trace carbon monoxide analyzer from AMETEK, with the minimum detection limit of carbon monoxide being 1 ppb.

[0117] The test data are listed in Table 3.

[0118] Table 1

[0119]

[0120] Table 2

[0121]

[0122] Table 3

[0123]

[0124] Comparative Examples 1 to 3 used commercially available alumina carriers to prepare catalysts. The commercially available alumina carriers had a small specific surface area (236 m 2 / g), the water absorption rate is small, and the copper content is low under the same catalyst preparation conditions as Examples 1, 3, and 4, respectively. The ability of Examples 1 to 4 and Comparative Example 1 to deeply remove trace CO is tested, and the test data are listed in Tables 1 to 3.

[0125] From Table 1, we can see that at 90℃, 3000hr -1 、4500hr -1 、10000hr -1 hour:

[0126] The outlet CO concentration of Example 1 is 18 ppb, 17 ppb, and 20 ppb, and the outlet CO concentration of Comparative Example 1 is 50 ppb, 52 ppb, and 89 ppb;

[0127] The outlet CO concentrations of Example 3 were 17ppb, 13ppb, and 13ppb, and the outlet CO concentrations of Comparative Example 2 were 53ppb, 51ppb, and 78ppb;

[0128] The outlet CO concentration of Example 4 is 13 ppb, 13 ppb, and 15 ppb, and the outlet CO concentration of Comparative Example 3 is 36 ppb, 45 ppb, and 68 ppb.

[0129] From Table 2, we can see that at 50℃, 3000hr -1 、4500hr -1 、10000hr -1 hour:

[0130] The outlet CO concentration of Example 1 is 30 ppb, 45 ppb, and 65 ppb, and the outlet CO concentration of Comparative Example 1 is 100 ppb, 120 ppb, and 180 ppb;

[0131] The outlet CO concentration of Example 3 is 25 ppb, 36 ppb, and 47 ppb, and the outlet CO concentration of Comparative Example 2 is 103 ppb, 131 ppb, and 140 ppb;

[0132] The outlet CO concentration of Example 4 is 23 ppb, 34 ppb, and 45 ppb, and the outlet CO concentration of Comparative Example 3 is 110 ppb, 145 ppb, and 168 ppb.

[0133] Comparing the above data, it can be seen that compared with the catalyst prepared using a commercially available alumina carrier under the same conditions, the catalyst prepared using the carbon-modified alumina carrier of the present invention has an ability to remove trace amounts of CO that is improved by about 3 to 5 times.

[0134] From the data after 200 hours of continuous reaction in Table 3, it can be seen that the catalyst prepared by the present invention has good stability.

[0135] The specific surface area of ​​the carbon-modified alumina carrier prepared in Examples 1 to 4 of the present invention reaches 448 to 469 m 2 / g. Compared with the alumina carrier of the prior art, the carbon-modified alumina carrier prepared in Examples 1 to 4 has a higher surface area, high water absorption, large amount of adsorbed metal, and high loading capacity, so the catalyst prepared by the impregnation method has higher metal dispersion, high reaction activity, and good stability.

Claims

1. A carbon-modified alumina carrier, the specific surface area of ​​the alumina carrier is ≥300m 2 / g, preferably 320 to 550 m 2 / g, more preferably 400 to 480 m 2 / g; pore volume is 1.0~3.5cm 3 / g, preferably 1.5 to 3.0 cm 3 / g.

2. A method for preparing the carbon-modified alumina carrier according to claim 1, comprising the following steps: (1) preparing sodium aluminate solution by sodium hydroxide and sodium aluminate, adding the solution to an aluminum sulfate solution, and mixing the mixture to obtain a boehmite precursor; (2) crystallizing the boehmite precursor obtained in step (1) to obtain boehmite; (3) The boehmite obtained in step (2) is post-treated and added to a nitrogen-containing polymer solution, and reacted after impregnation, and the obtained reaction product is calcined in a protective gas atmosphere to obtain the carbon-modified alumina carrier.

3. The method for preparing a carbon-modified alumina carrier according to claim 2, characterized in that: Step (1), The concentration of aluminum ions in the sodium aluminate solution is 0.1 to 0.9 mol / L, preferably 0.3 to 0.9 mol / L; and / or, The sodium-aluminum molar ratio in the sodium aluminate solution is (2-6):1, preferably (2-5):1; and / or, The method of adding is dropwise addition; and / or, The concentration of the aluminum sulfate solution is 0.1 to 0.9 mol / L, preferably 0.3 to 0.6 mol / L; and / or, The amount of sodium aluminate solution added is such that the pH value reaches 8 to 11; and / or, The mixing temperature is 10-35° C., the mixing time is 10-60 min, and the mixing method is stirring. Preferably, the stirring speed is 200-800 rpm.

4. The method for preparing a carbon-modified alumina carrier according to claim 2, characterized in that: Step (2), The crystallization temperature is 50 to 120° C., preferably 70 to 120° C.; and / or, The crystallization time is 2 to 24 hours, preferably 5 to 20 hours.

5. The method for preparing a carbon-modified alumina carrier according to claim 2, characterized in that: Step (3), The post-treatment methods include filtering, washing, and drying; and / or, The nitrogen-containing polymer is at least one of polyvinyl imidazole, polyvinyl pyrrolidone and polyvinyl pyridine; and / or, The solvent in the nitrogen-containing polymer solution is at least one of methanol and ethanol; and / or, The mass ratio of the boehmite to the nitrogen-containing polymer is (1-100):1, preferably (5-100):1, more preferably (10-100):1; and / or, The reaction temperature is 80 to 150°C, preferably 100 to 120°C; and / or, The reaction time is 4 to 10 hours, preferably 5 to 10 hours; and / or, The concentration of the nitrogen-containing polymer solution is 0.1 to 2 wt%, preferably 0.6 to 1.8 wt%; and / or, The protective gas is nitrogen or an inert gas; and / or, The immersion temperature is 10 to 35°C and the immersion time is 0.5 to 2 hours; and / or, The calcination temperature is 400-600°C, and the calcination time is 3-10h.

6. A carbon-modified alumina carrier obtained by the preparation method according to any one of claims 2 to 5.

7. A catalyst comprising the carbon-modified alumina carrier according to claim 1 or 6, wherein the catalyst further comprises an active component, and preferably further comprises an auxiliary component; further preferably, The active component includes Cu; and / or, The auxiliary agent component is at least one of Zn, Mg, Ni, Co, Mn, and Co; More preferably, Taking the total mass of the catalyst as 100%, the catalyst comprises: Carbon-modified alumina support 30-90%; preferably 55-70%; Active ingredient 10-60%; preferably 25-40%; The auxiliary component is 0-10%, preferably 0-6%.

8. A method for preparing the catalyst as claimed in claim 7, comprising: The carbon-modified alumina carrier is contacted with a solution or a mixed solution containing an active component, preferably the solution or the mixed solution also includes an auxiliary component, and the carbon-modified alumina carrier after contact is taken out and then subjected to a second calcination under a protective gas atmosphere to obtain the carbon-modified alumina carrier catalyst.

9. The method for preparing the catalyst according to claim 8, characterized in that: The mixed solution containing the active component is a mixed solution composed of a solution containing the active component and a solution containing the auxiliary component; further preferably, the mass percentage of the water-soluble salt of the active component in the solution containing the active component is 30-60wt%; the mass percentage of the water-soluble salt of the auxiliary component in the solution containing the auxiliary component is 1-8wt%, preferably 4-6wt%; and / or, The temperature of the contact between the solution or mixed solution containing the active component and the carbon-modified alumina support is 15 to 40° C. and the time is 10 to 60 minutes; and / or, The solution or mixed solution containing the active component is contacted with the carbon-modified alumina support by at least one of immersion and spraying; and / or, The carbon-modified alumina support is contacted with a solution or a mixed solution containing active components, and the product is subjected to a second drying and then a second calcination; preferably, the second drying temperature is 100 to 130° C. and the time is 8 to 15 hours; and / or, The protective gas is at least one of nitrogen and an inert gas; the inert gas is preferably at least one of argon and helium; and / or, The second calcination is carried out at a temperature of 400 to 800° C. and for a time of 2 to 10 hours.

10. A catalyst obtained by the preparation method according to claim 8 or 9.

11. A method for deep removal of trace CO, comprising: The material containing CO is contacted with the catalyst according to claim 7 or 10 to remove CO.

12. The method for deep removal of trace CO according to claim 11, characterized in that: The CO content of the CO-containing material is 0.01 ppm to 200 ppm, preferably 0.01 to 100 ppm, more preferably 0.01 to 10 ppm, most preferably 0.1 to 5 ppm; and / or, The reaction temperature is 0 to 150°C, preferably 20 to 120°C; and / or, The reaction pressure is 0.1-5 MPa, preferably 0.1-3 MPa; and / or the volume space velocity during the gas phase reaction is 1000-10000 h -1 and / or, The volume space velocity during liquid phase reaction is 1 to 150 h -1 .

Citation Information

Patent Citations

  • Alumina catalyst support

    CN103260747A

  • Hydrogenation catalyst with high denitrification performance and preparation method therefor

    CN105983412A

  • Alumina carrier and preparation method thereof

    CN106669645A

  • Method for removing carbon monoxide

    CN116036854A

  • Carbon-modified aluminum oxide microsphere-loaded catalyst as well as preparation method and application thereof

    CN116037181A